Impact of famine during pregnancy and infancy on health in adulthood - Yang, Z.; Zhao, W.; Zhang, Xiaobo; Mu, Ren; Zhai, Y.; Kong, L.; Chen, C. (Wiley, 2008)
The objectives of the present study are (i) To examine the association between fetal nutritional status and overweight and obesity in adulthood and (ii) to provide the evidence for formulating a strategy to prevent low birth weight. With data from the 2002 Nationwide Nutrition and Health Survey, the body mass indexes (BMIs) of rural residents born during the famine years of 1959, 1960, 1961 were compared with those born in 1964. The health consequence of famine on the adulthood BMI was evident in women; the mean BMIs of the women were significantly higher in the three famine groups than that in the control group born in 1964 (P < 0.01). After adjustment for regional differences within China, the prevalences of overweight in women were significantly higher in the three famine groups (P < 0.01) and of obesity in the 1959 and 1960 groups. (P < 0.01). Such differences were not found in men. The higher risks of overweight and obesity in women were caused by malnutrition in fetal life. A strategy for preventing low birth weight should be formulated by the government to prevent chronic disease in adulthood.